Developing multidisciplinary clinics for neuromuscular care and research. Issue 5 (29th August 2017) - Paganoni, Sabrina; Nicholson, Katie; Leigh, Fawn; Swoboda, Kathryn; Chad, David; Drake, Kristin; Haley, Kellen; Cudkowicz, Merit; Berry, James D.
ABSTRACT: Multidisciplinary care is considered the standard of care for both adult and pediatric neuromuscular disorders and has been associated with improved quality of life, resource utilization, and health outcomes. Multidisciplinary care is delivered in multidisciplinary clinics that coordinate care across multiple specialties by reducing travel burden and streamlining care. In addition, the multidisciplinary care setting facilitates the integration of clinical research, patient advocacy, and care innovation (e.g., telehealth). Yet, multidisciplinary care requires substantial commitment of staff time and resources. We calculated personnel costs in our ALS clinic in 2015 and found an average cost per patient visit of $580, of which only 45% was covered by insurance reimbursement. In this review, we will describe classic and emerging concepts in multidisciplinary care models for adult and pediatric neuromuscular disease. We will then explore the financial impact of multidisciplinary care with emphasis on sustainability and metrics to demonstrate quality and value . Muscle Nerve 56 : 848–858, 2017